Trajectory tracking controller for quadrotors without velocity and angular velocity measurements. Issue 1 (1st January 2017) - Zou, Yao
Abstract : This study presents a non‐linear trajectory tracking controller for quadrotors without velocity and angular velocity measurements. The rotation matrix is utilised to represent the quadrotor attitude. Based on the hierarchical control strategy, the position and attitude loops are investigated separately, where two novel auxiliary systems are, respectively, introduced to obviate usage of the velocity and angular velocity information in the corresponding control developments. In addition, a criterion for choosing the position loop control parameters is established to ensure the singularity‐free extraction of the command rotation matrix. Further, an attitude control scheme with the initial condition constraint is exploited to ensure the attitude tracking error converging to the desired equilibrium all the time. In terms of the hierarchical system synthesis theory, it is demonstrated that the quadrotor, with the proposed controller, is able to accomplish trajectory tracking manoeuvres with asymptotically stable property. Finally, simulations verify theoretical results.